Damage to roots and collars of broadleaf woody plants - Glavendekic, M.; Matsiakh, I.; Lakatos, F.; Csoka, G.; Moreira, A. C.; Lehtijaervi, Asko Tapio (Cabi Publishing-C A B Int, 2017)
[No Abstract Available]
Keywords: [No Keywords]